Voice in the Context of Literacy Studies - Sperling, Melanie; Appleman, Deborah (Reading research quarterly, 2011)
The concept of voice permeates perspectives on reading and writing and has helped guide both literacy research and teaching. However, what voice is for scholars, researchers, and teachers takes many guises, some in apparent contradiction to others. We offer a theoretical perspective on the concept of voice, situating it within sociocultural accounts of language and literacy and, through a review of language and literacy research, arrive at a definition of voice. In doing so, we discuss the varied rhetorical, linguistic, and educational foundations of voice, exploring individual-centered and social- and cultural-centered perspectives, and two differing premises driving research: that voice is a quality of language that reflects authorial choice and can be taught, and that voice is a lens for understanding reading, writing, and learning processes. We discuss implications of our thinking about voice for literacy research and teaching.